ANXIETY IN D.H LAWRENCE’S ”LADY CHATTERLEY’S LOVER”: A PSYCHOANALYTIC APPROACH - RATMAWATI , SEFTY DWI (2007)

(untitled)
The major problem of this study is to eludicate how anxiety of lady Chatterley is reflected in D.H Lawrence Lady Chatterley Lovers. The objectives of the study are to analyze the novel based on their psychoanalytic approach.